LncRNA-uc002mbe.2 Interacting with hnRNPA2B1 Mediates AKT Deactivation and p21 Up-Regulation Induced by Trichostatin in Liver Cancer Cells - Chen, Ting; Gu, Chengxin; Xue, Cailin; Yang, Tao; Zhong, Yun; Liu, Shiming; Nie, Yuqiang; Yang, Hui (Frontiers in Pharmacology, 2017)
Long non-coding RNAs (lncRNAs) have been implicated in liver carcinogenesis. We previously showed that the induction of lncRNA-uc002mbe.2 is positively associated with the apoptotic effect of trichostatin A (TSA) in hepatocellular carcinoma (HCC) cells. The current study further analyzed the role of uc002mbe.2 in TSA-induced liver cancer cell death. The level of uc002mbe.2 was markedly increased by TSA in the cytoplasm of HCC cells. Knockdown of uc002mbe.2 prohibited TSA-induced G2/M cell cycle arrest, p21 induction, and apoptosis of Huh7 cells and reversed the TSA-mediated decrease in p-AKT. RNA pull-down and RNA-binding protein immunoprecipitation (RIP) assays revealed that TSA induced an interaction between uc002mbe.2 and heterogeneous nuclear ribonucleoprotein A2B1 (hnRNPA2B1) in Huh7 cells. This interaction mediated AKT deactivation and p21 induction in liver cancer cells. In an athymic xenograft mouse model, knockdown of uc002mbe.2 significantly prohibited the TSA-mediated reduction in tumor size and weight. In addition, the ability of TSA to reduce hnRNPA2B1 and p-AKT levels and induce p21 in the xenograft tumors was prevented by uc002mbe.2 knockdown. Therefore, the interaction of uc002mbe.2 and hnRNPA2B1 in mediating AKT deactivation and p21 induction is involved in the cytostatic effect of trichostatin in liver cancer cells.